Exploring determinants of community pharmacist-led influenza vaccination in a Middle Eastern country: a national web-based cross-sectional study - Dalal Youssef; Linda Abou-Abbas; Hamad Hassan (Taylor & Francis Group, 2021)
Background Utilizing community pharmacists (CPs) as immunizers has being adopted in various countries as approach to boost influenza vaccination coverage. Our study aims to explore the Lebanese CPs' willingness to administer influenza vaccine, and to identify factors associated with this willingness. Methods This is a web-based, cross-sectional study, conducted over 2 months, from the 1st of November to the end of December 2020. Self-reported data were collected electronically from Lebanese CPs through an anonymous, questionnaire using google form. The collected data were analyzed using the statistical software SPSS (Statistical Package for Social Sciences). Bivariate and multivariable analyses were performed to examine factors associated with the willingness of CPs to administer influenza vaccine. Results A total of 412 CPs participated in this survey of which 76.9% are willing to administer influenza vaccines. More than 90% of them had a good overall knowledge score and 88.8% of CPs showed a positive overall attitude score, particularly towards involvement of CPs in influenza vaccine provision. Their willingness to administer vaccine was positively associated with the younger age (aOR = 3.12 with 95% CI (1.597-4.040)), higher education level (aOR = 2.02 with 95% CI (1.093-3.741)), previous experience in immunization (aOR = 2.72 with 95% CI (1.320-5.627)) and urbanicity of pharmacy (aOR = 1.542 with 95% CI (1.219-4.627)). Extensive working hours (aOR = 2.34 with 95% CI (1.131-4.845)), working in pharmacies that are operating round-the-clock, showing positive attitude towards immunization (aOR = 3.01 with 95% CI (1.872-6.422)) and towards provision of influenza vaccines (aOR = 13.72 with 95% CI (13.721-38.507)) were also positively associated to this willingness. Conversely, patient privacy (aOR = 0.55 with 95% CI (0.079-0.983)), time and cost for professional development (aOR = 0.55 with 95% CI (0.172-0.918)), limited patient's trust (aOR = 0.39 with 95% CI (0.203-0.784)), financial remuneration (aOR = 0.18 with 95% CI (0.088-0.377)), and requirement of formal certification in vaccine administration (aOR = 0.07 with 95% CI (0.020-0.279)) were negatively associated to this willingness. Conclusion Addressing the unearthed concerns related to utilizing CPs as influenza immunizers through a concerted effort is a key to success in any future implementation of vaccination services in pharmacies.